1993
DOI: 10.2527/1993.711164x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of endophyte-infected tall fescue consumption on diet utilization and thermal regulation in cattle

Abstract: Two experiments were conducted to determine the effects of endophyte fungus (Acremonium coenophialum) ingestion in tall fescue diets and environmental temperature on heat dissipation and diet utilization by cattle. In Exp. 1, 12 Angus heifers (average weight 244 kg) were allotted by weight to either an endophyte-free (E-) or endophyte-infected (E+; 381 ppb of ergovaline) diet. Environmental temperature varied between 22 and 32 degrees C. Voluntary DM and water intakes were similar (P > .10) among treatments. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 18 publications
13
86
1
2
Order By: Relevance
“…A ocorrência de hipertermia em bovinos associada à ingestão de ergoalcalóides ocorre devido à ação vasoconstritora periférica dessas micotoxinas que reduz o fluxo do sangue para a pele e a perda de calor na periferia (Osborn et al 1992, Paterson et al 1995, Browning Jr. et al 1998b. Essa hipótese é consubstanciada pelo fato de que a administração experimental de ergoalcalóides a bovinos mantidos em temperaturas de 32°C reduz a evaporação da pele (Aldrich et al 1993). A administração de ergotamina, o principal ergoalcalóide de C. purpurea, para bovinos mantidos em temperatura de 30°C promove o aumento da freqüên-cia respiratória, decréscimo na temperatura da pele e elevação da temperatura retal (Osborn et al 1992.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A ocorrência de hipertermia em bovinos associada à ingestão de ergoalcalóides ocorre devido à ação vasoconstritora periférica dessas micotoxinas que reduz o fluxo do sangue para a pele e a perda de calor na periferia (Osborn et al 1992, Paterson et al 1995, Browning Jr. et al 1998b. Essa hipótese é consubstanciada pelo fato de que a administração experimental de ergoalcalóides a bovinos mantidos em temperaturas de 32°C reduz a evaporação da pele (Aldrich et al 1993). A administração de ergotamina, o principal ergoalcalóide de C. purpurea, para bovinos mantidos em temperatura de 30°C promove o aumento da freqüên-cia respiratória, decréscimo na temperatura da pele e elevação da temperatura retal (Osborn et al 1992.…”
Section: Resultsunclassified
“…Esses sinais clínicos também regulatórias (Browning Jr et al 1998b). No entanto, bovinos expostos naturalmente aos alcalóides do ergot por períodos prolongados não apresentam variações nas concentrações plasmáticas de T3, T4 e cortisol (Aldrich et al 1993).…”
Section: Discussionunclassified
“…Both the endophyte and added ergotamine decreased peripheral body temperature; this was attributed to reduced peripheral blood flow. Similar changes in rectal temperature in cattle resulted from feeding E+ or E-tall fescue diets when animals were exposed to diurnal temperature changes (Aldrich et al 1993a). Interestingly, this experiment also revealed that there was a significant interaction between diet and environmental temperature on skin vaporization; with skin vaporization increased only in the E-group at an elevated temperature.…”
Section: Discussionmentioning
confidence: 98%
“…Chestnut et al (1991) found no difference in organic matter digestibility of E+ and E-tall fescue in steers and Harmon et al (1991) found no endophyte effect on dry matter and nitrogen digestibility in steers. Others, however, found that diets containing E+ tall fescue had reduced dry matter and organic matter digestibility in sheep (Hannah et al 1990, Fiorito et al 1991, Westendorf et al 1993, cattle (Aldrich et al 1993a), and rats (Larson et al 1991), which could be ambient temperaturedependent (Hannah et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The varieties we seeded were similar to those cited in the following references. In 2006, we planted replicated monocultures of TF (Festuca arundinaceum, Kentucky 31 endophyte-infected and endophyte-free TFs; Rottinghaus et al, 1991;Aldrich et al, 1993) and RCG (Phalaris arundinacea L. varieties v.n.s. and palaton) high (1) and low (2) in alkaloids, respectively (Marten, 1972;Sheaffer et al, 1990); BFT (Lotus corniculatus varieties Goldie and Norcen) high (1) and low (2) in tannins, respectively (Terrill et al, 1992;Hedqvist et al, 2000); and ALF (Medicago sativa varieties Vernal and Lahontan) high (1) and low (2) in saponins, respectively (Pedersen, 1975;Pedersen et al, 1976; Table 1).…”
Section: Pasture Designmentioning
confidence: 99%